Teachers' views of the impact of school evaluation and external inspection processes. (March 2016) - Hopkins, Elizabeth; Hendry, Helen; Garrod, Frank; McClare, Siobhan; Pettit, Daniel; Smith, Luke; Burrell, Hannah; Temple, Jennifer
The research explores the views of teachers about how their teaching is evaluated by others. The tensions between evaluations motivated by the drive to improve practice (school self-evaluation) and evaluation related to external accountability (external evaluation – inspection) are considered, linked to findings and ideas reported in the literature. The study was undertaken using interviews (which included reflection on critical incidents during inspection) and incorporated the use of drawings as a research tool. Much of the data gathering and analysis were undertaken by five Third-Year undergraduate Education Studies students working under the direction and tutorage of the author (Hopkins). The findings validated those reported in the literature about the negative experiences of external evaluation (inspection) and point towards ways in which these might be reduced. The use of drawings alongside semistructured interviews proved to be a particularly powerful means of eliciting teachers' thinking and feeling. The involvement of undergraduates as co-researchers provided them with a rich and authentic opportunity to gain insights into the professional world of teachers which they were preparing to join.